Near-peer mentorship for undergraduate training in Ugandan medical schools: views of undergraduate students - Zari Rukundo, Godfrey; Burani, Aluonzi; Kasozi, Jannat; Kirimuhuzya, Claude; Odongo, Charles; Mwesigwa, Catherine; Byona, Wycliff; Kiguli, Sarah (Pan African Medical Journal, 2016)
Masters Students are major stakeholders in undergraduate medical education but their contribution has not been documented in Uganda. The aim of the study was to explore and document views and experiences of undergraduate students regarding the role of masters students as educators in four Ugandan medical schools. Methods: This was a cross-sectional descriptive study using qualitative data collection methods. Eight Focus Group Discussions were conducted among eighty one selected preclinical and clinical students in the consortium of four Ugandan medical schools: Mbarara University of Science and Technology, Makerere College of Health Sciences, Gulu University and Kampala International University, Western Campus. Data analysis was done using thematic analysis. Participants' privacy and confidentiality were respected and participant identifiers were not included in data analysis. Results: Undergraduate students from all the medical schools viewed the involvement of master's students as very important. Frequent contact between masters and undergraduate students was reported as an important factor in undergraduate students' motivation and learning. Despite the useful contribution, master' students face numerous challenges like heavy workload and conflicting priorities. Conclusion: According to undergraduate students in Ugandan medical schools, involvement of master's students in the teaching and learning of undergraduate students is both useful and challenging to masters and undergraduate students. Masters students provide peer mentorship to the undergraduate students. The senior educators are still needed to do their work and also to support the master's students in their teaching role.
Keywords: Undergraduate medical education; Near peer mentorship; Ugandan medical education